2010
DOI: 10.1517/17530059.2010.506509
|View full text |Cite
|
Sign up to set email alerts
|

Molecular testing in transfusion medicine

Abstract: At present, molecular methods complement serologic antigen determination and are an invaluable tool for specific diagnostic problems. Mass-scale molecular antigen prediction of blood donors is beginning to improve blood supply for specific patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 115 publications
(97 reference statements)
0
6
0
1
Order By: Relevance
“…A few reports have shown that genotyping is more accurate than phenotyping, and the outcome of a genotyping error (e.g. Jk null) would predict an antigen‐positive unit, which would not harm the patient (Wagner, ). On the other hand, phenotyping errors are relatively common for the Fyb and U antigens.…”
Section: The Future Of Genotype Dry Matchingmentioning
confidence: 99%
“…A few reports have shown that genotyping is more accurate than phenotyping, and the outcome of a genotyping error (e.g. Jk null) would predict an antigen‐positive unit, which would not harm the patient (Wagner, ). On the other hand, phenotyping errors are relatively common for the Fyb and U antigens.…”
Section: The Future Of Genotype Dry Matchingmentioning
confidence: 99%
“…Highly accurate platforms are the best fit for red cell genotyping of patients in elective situations; they can be licensed as tests of record but tend to be elaborate and low throughput (Avent et al , 2009, Hashmi et al , 2005). For mass scale donor typing, the largest datasets were established using methods optimized for low cost and high throughput screening, correcting for inaccuracies by targeted serological checks (Flegel et al , 2015b, Wagner 2010, Perreault et al , 2009). For patients with urgent transfusion needs, we reasoned that the decisive feature was turnaround time (Flegel et al , 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular immunohematology methods are increasingly used to determine blood group antigens in routine patient care. Established first line indications for red cell genotyping include prenatal diagnosis, such as the prediction of the fetus' phenotype from the mother's peripheral blood; blood group phenotypes that cannot be discriminated by serology; and blood group typing in recipients of massive or chronic transfusions (Denomme & Flegel, 2008;Wagner, 2010). Direct polymerase chain reaction (PCR) has been applied to blood donor typing using heat-treated plasma samples without DNA isolation (Silvy et al, 2015), a simple but not rapid procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several available molecular methods can identify a greater number of antigens than can be determined by any blood group serology. 10,13,14 Red cell genotyping provides an opportunity to integrate antigen testing into other molecular testing of blood donors, 15,16 and has been applied to a limited degree outside of the US for routine typing and labeling of blood since 2002. 17 …”
Section: Introductionmentioning
confidence: 99%